2011
DOI: 10.1103/physrevb.83.094102
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and phase transitions in ferroelectrictris-sarcosine calcium chloride and its brominated isomorphs

Abstract: Tris-sarcosine calcium chloride [(TSCC), (CH 3 NHCH 2 COOH) 3 CaCl 2 ] is a uniaxial ferroelectric (FE) with a displacive second-order phase transition near T c = 130 K. A continuous range of solid solutions can be made by substituting Br for Cl, which lowers T c to 0 K at ∼72% Br. Such a quantum critical point differs from that in pseudocubic FEs, such as O-18 SrTiO 3 or doped KTaO 3 . For many years, this system was thought to have only two phases, paraelectric and FE, at ambient pressure. However, we find f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…This was first described by Bornarel, Lajzerowicz, and Legrand (1974), who found that in such cases ferroelectric polar domain walls could strongly interact with nearby ferroelastic nonpolar walls, tilting both walls and making the nonpolar walls slightly polar. This was recently demonstrated rather spectacularly in ferroelectric tris-sarcosine calcium chloride by Jones et al (2011). Of relevance here is also the fact that ferroelectric domain walls are easily pinned by defects and vacancies, so the switching properties and dielectric contribution of the walls can be modified by manipulating the dopant chemistry.…”
Section: Switching Of Domainsmentioning
confidence: 79%
“…This was first described by Bornarel, Lajzerowicz, and Legrand (1974), who found that in such cases ferroelectric polar domain walls could strongly interact with nearby ferroelastic nonpolar walls, tilting both walls and making the nonpolar walls slightly polar. This was recently demonstrated rather spectacularly in ferroelectric tris-sarcosine calcium chloride by Jones et al (2011). Of relevance here is also the fact that ferroelectric domain walls are easily pinned by defects and vacancies, so the switching properties and dielectric contribution of the walls can be modified by manipulating the dopant chemistry.…”
Section: Switching Of Domainsmentioning
confidence: 79%
“…16 On the other hand the constrained-GGA results in U = 0.8 eV in case of the Co/CuN system. 7 We also note that a common practice is to use the U and J H as fitting parameters to achieve the best agreement with known experimental data. For instance, the LDA + U method with U = 5.88 eV gives the isotropic exchange interactions between Mn atoms on the CuN surface that agree well with experimental estimates.…”
Section: -2mentioning
confidence: 97%
“…4,6 The next step toward realistic modeling of Mn/CuN, Fe/CuN, and Co/CuN systems would be to take into account the orbital nature of the adatom and hybridization effects between the adatom and surface states. This can be done by using a density functional theory (DFT) method 7 or a many-body Anderson impurity model approach, or their combination. The first-principles DFT-based calculations provide important information concerning ground state properties of the surface nanosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSCC (tris-sarcosine calcium chloride) has a second-order displacive paraelectric (PE) to ferroelectric (FE) phase transition near T c = 130 K. 1,2 Early work by Bornarel and Schmidt 3 showed that trissarcosine calcium chloride also has a structural phase transition at ca. 700 MPa hydrostatic pressure at T=293 K and that the phase boundary extrapolates to << 40K at atmospheric pressure (their studies were limited to T > 77 K).…”
Section: Introductionmentioning
confidence: 99%